When the Gated Misbehave: Online reader comments on Anthony Weiner's sexting scandal. (21st October 2018) - Erzikova, Elina; Simpson, Edgar
Abstract : This study analyzes online reader comments on top US newspapers' stories related to former congressman, Anthony Weiner's, August 2016 sexting scandal. Audience gatekeeping was seen through such discussion themes as gender bias and sexism, political scandals, and sex addiction. The analysis revealed that the majority of reader comments significantly diverged from the news topic, and many comments about US politicians were uncivil. Furthermore, online discussions "drowned out" newspapers' intended message about Weiner's inclusion of his toddler son into a sexually explicit selfie. This study argues that online commentary should not be perceived as a dichotomy—a negative or positive development, a contributor or preventer of public discourse—but rather as a continuum of citizen engagement.